Anatomy & physiology coloring book: a complete study guide - Marieb, Elaine N. (Singapore : Addision-Wesley Publishing Company, 2001)
Combining a wide range and variety of engaging coloring activities, exercises, and self-assessments into an all-in-one Study Guide, the Anatomy and Physiology Coloring Workbook helps you simplify your study of A&P. Featuring contributions from new co-author Simone Brito, the 12th edition of this best-selling guide continues to reinforce the fundamentals of anatomy and physiology through a variety of unique, interactive activities. You now benefit from new crossword puzzles in each chapter, along with dozens of strengthened and expanded exercises, illustrations, and over 100 coloring exercises. Additional self-assessments, (3z(BAt The Clinic(3y (Bshort answer questions, and unique (3z(BIncredible Journey(3y (Bvisualization exercises, further reinforce basic concepts that are relevant to health care careers.s
The human body : an orientation -- Basic chemistry -- Cells and tissues -- Skin and body membranes -- The skeletal system -- The muscular system -- The nervous system -- Special senses -- The endocrine system -- Blood -- The cardiovascular system -- The lymphatic system and body defenses -- The respiratory system -- The digestive system and body metabolism -- The urinary system -- The reproductive system.
Keywords: HUMAN ANATOMY -- PROBLEMS, EXERCISES, ETC